2015
DOI: 10.1002/jcp.24971
|View full text |Cite
|
Sign up to set email alerts
|

Pantethine Alters Lipid Composition and Cholesterol Content of Membrane Rafts, With Down‐Regulation of CXCL12‐Induced T Cell Migration

Abstract: Pantethine, a natural low-molecular-weight thiol, shows a broad activity in a large range of essential cellular pathways. It has been long known as a hypolipidemic and hypocholesterolemic agent. We have recently shown that it exerts a neuroprotective action in mouse models of cerebral malaria and Parkinson's disease through multiple mechanisms. In the present study, we looked at its effects on membrane lipid rafts that serve as platforms for molecules engaged in cell activity, therefore providing a target agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…At least part of the mechanism leading to Il-1 expression requires the translocation of NF-B to the nucleus that can be achieved after binding of A 42 to TLR2. Although the mechanism of action of pantethine is not yet elucidated, it was shown that pantethine alters lipid composition and cholesterol content of membrane rafts (96). Such an alteration with methyl--cyclodextrin was reported to decrease the levels of nuclear translocation of NF-B p65, phosphorylated ERK1/2 and TLR4 (97, 98).…”
Section: Discussionmentioning
confidence: 99%
“…At least part of the mechanism leading to Il-1 expression requires the translocation of NF-B to the nucleus that can be achieved after binding of A 42 to TLR2. Although the mechanism of action of pantethine is not yet elucidated, it was shown that pantethine alters lipid composition and cholesterol content of membrane rafts (96). Such an alteration with methyl--cyclodextrin was reported to decrease the levels of nuclear translocation of NF-B p65, phosphorylated ERK1/2 and TLR4 (97, 98).…”
Section: Discussionmentioning
confidence: 99%
“…It was recently shown that pantethine affects lipid raft composition causing a decline of the proportion of saturated fatty acid, an increase in mono- and polyunsaturated fatty acid, and a decrease of cholesterol content (17). These changes in raft composition led to an impairment of CXCL12 to bind to its target (17).…”
Section: Discussionmentioning
confidence: 99%
“…These changes in raft composition led to an impairment of CXCL12 to bind to its target (17). The CXCL12–CXCR4 axis promotes proliferation, migration, invasion, and metastasis in ovarian cancer (37), therefore its alteration by pantethine may be a mechanism for the reduction of metastases observed in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike pantothenate, pantothine may stimulate CoA biosynthesis via PANK-independent mechanisms (51). In addition, pantethine may be able to modulate inflammation and oxidative stress independently of its effects on CoA synthesis (52). …”
Section: Discussionmentioning
confidence: 99%